Analysis Of The Success Of Shopee E-Commerce Using The Delone & Mclean Is Success Model - azzahra; Veri, Jhon (Riset Sinergi Indonesia, 2025)
Shopee was the marketplace with the most daily visits in December 2021, namely 33.27 million times, dominated by those aged 20 - 24 years according to the Jakpat survey. If categorized, this age group includes students, workers and local communities. Many people have not taken advantage of business opportunities on Shopee because of a lack of knowledge. By conducting this research, it is hoped that it can provide recommendations and information on Shopee's success so that it attracts user interest. The Delone & Mclean IS Success Model has six variables, namely system quality, information quality, service quality, usage, user satisfaction, and net benefits to measure success. By testing the application using DeLone and McLean, it is known that the Shopee application as a whole has a very good quality system and a score of 95%.